Greening the ocean economy - Barbier, Edward B. (Frontiers in Environmental Economics, 2023)
The ocean economy comprises a wide range of industries—fishing, offshore energy, mineral extraction, shipping and coastal tourism. It generates 1.5 trillion in global value added and is expected to double in size by 2030. If we are to successfully green the ocean economy, we must overcome two major distortions—the underpricing of marine capital and the underfunding of ocean and coastal conservation. Many important values provided by the marine environment are ignored or discounted in our decisions to exploit, convert and pollute our coastlines and seas. The funding gap between current financing of conservation, restoration and sustainable management of marine capital and the most critical funding needs is estimated at 120–154 billion annually. We urgently need a new global agreement for oceans and coasts that has three principal aims: (1) Phasing out subsidies for fishing, extractive activities, and other ocean industries. (2) Implementing market-based incentives, management reforms, and other regulations to reduce any remaining ecological marine damages. (3) Using any financial savings and revenues generated to support global funds and investments for conserving, restoring and protecting marine capital in an inclusive manner. There should also be more participation by the private sector in developing global marine and in bridging the funding gap for marine conservation. It is estimated that major companies in ocean industries could raise an additional 83–186 billion each year for marine conservation investment that would also benefit their financial interests and markets.